Assessing estuarine environmental quality using fish-based indices: Performance evaluation under climatic instability - Martinho, F. (2008)
http://www.sciencedirect.com/science/article/B6V6N-4TFDY7X-2/2/c9f9bbc565621cbb798d6d663e74a8fa